Mesoproterozoic fluid events affecting Archean crust in the northern Olympic Cu–Au Province, Gawler Craton: insights from 40Ar/39Ar thermochronology. Issue 1 (2nd January 2017) - Reid, A. J.; Jourdan, F.; Jagodzinski, E. A.
ABSTRACT: The Olympic Cu–Au Province, Gawler Craton, is host to the Olympic Dam and Prominent Hill iron oxide–copper–gold (IOCG) deposits. Both of these deposits and the region between the two are covered by Neoproterozoic to Cenozoic sediment, making inferences about prospectivity in this portion of the Olympic Domain reliant on geophysical interpretation and sparse drill hole information. We present new U–Pb zircon sensitive high resolution ion microprobe (SHRIMP) dates from two basement intersecting drill holes in the region between Olympic Dam and Prominent Hill that show bimodal volcanism occurred at 2555 ± 5 Ma, and was followed by intrusion of tonalite at 2529 ± 6 Ma. Laser 40 Ar/ 39 Ar dating of biotite and muscovite from the tonalite yields ages around ca 2000 Ma, consistent with slow cooling trends observed in Archean rocks elsewhere in the northern Gawler Craton. Step heating experiments on K-feldspar from the same tonalite yields an age spectrum with older ages around 1740 Ma from the highest temperature steps becoming progressively younger to a minimum of 1565 Ma in the lowest temperature heating steps; this is consistent with either Paleoproterozic cooling to final closure of K-feldspar by 1565 Ma or a reheating event at ca 1565 Ma, with the latter more likely, given the evidence for sub-solidus alteration of the K-feldspar. Sericite within hematite–sericite–chlorite altered portions of the tonalite yield a poorly defined age of ca 1.6 Ga. Taken together the 40 Ar/ 39 Ar data providing evidence for a fluid event affecting this region between Olympic Dam and Prominent Hill during the early Mesoproterozoic. Low temperature quartz–carbonate–adularia veins occur in <10 cm wide fractures within basalt in one drill hole in this region. Adularia from these veins yields 40 Ar/ 39 Ar ages that span from ca 1.3–1.1 Ga. This age range is interpreted to approximate either the timing of adularia formation during a hydrothermal event or the timing of resetting of the 40 Ar/ 39 Ar systematics within the adularia as a result of fluid flow in this sample. This is evidence for a mid-Mesoproterozoic fluid event in the Gawler Craton and necessitates a reconsideration of the long-term stability of the craton, as it appears to have been affected, at least locally, by fluid flow related to a much larger event within the Australian continent, the Musgrave Orogeny.